Efeitos da temperatura e adesivos na qualidade de painéis aglomerados produzidos com resíduos de madeira de eucalipto - Tinti, Vinicius Peixoto (2015)
The objective of the research was to evaluate the use of sawmill residue in the production of particleboard with adding commercial chemical adhesives modified tannin of Acacia mearnsii De Willd. Eucalyptus wood waste was obtained in an existing sawmill in Caparaó region, south of the Espírito Santo state. It was used sawdust from lumber trimmer, which were chemically analyzed for pH, buffer capacity, extractives and ash. The sawdust was dried in air until a moisture content of approximately 15%, and then sieved and the particles which were used in the pierced mesh were 4.0mm and 2.0mm retained on. The particles were dried in an oven at 103 ± 2°C until the preset humidity of 5% and used for the production of panels with dimensions of 42.5 x 42.5 x 1.25 cm and a nominal density of 700 kg m-3 . Were determined in pure commercial adhesives (phenol formaldehyde and urea), and combinations thereof with 10 to 20% of dilute tannin (tannin solution of 50% - tannin: distilled water), solids content, pH and viscosity. The statistical design was completely randomized in a factorial arrangement (7x2), and the temperature on two levels and the adhesive on 7 levels, and carried out the analysis of variance for all tests, except for the X-ray densitometry. With the produced particleboards proceeded to assess the physical and mechanical properties, biodeterioration by fungi and termites (dry-wood termites), and the density profile by X-ray densitometry. The bulk density of the panel was below the nominal predetermined, a fact explained by the presence of bark on the particles. For thickness swell test after 2 hours, only four of the adhesive 14 were below the standard required by the commercial American 236- 6 but for the thickness swell test after 24 hours, seven adhesives have not reached the set by the standard. For the modulus of rupture (MOR) have not reached five adhesive regulated by the American Standard ANSI A208.1, and modulus of elasticity (MOE) only 3 adhesives showed satisfactory results according to the same standard. The internal connection obtained results within the American Standard ANSI A208.1. In screw pullout on the surface only the tannin phenol formaldehyde adhesive 80:20 (120°C) obtained value below the American Standard ANSI A208.1. In the deterioration caused by the fungus Postia placenta adhesives with 100% tannin formaldehyde (120 and 140°C) had the greatest loss of mass and the fungus Trametes versicolor mass loss was high (above 20%) for most adhesives except for phenol formaldehyde (100%) phenol and tannin formaldehyde (90:10). The evaluation of density profile with the technique of the X-ray densitometry showed homogeneity between the panels, observed by proximity of the lines of profiles.